Vildagliptin vs sulfonylurea in Indian Muslim diabetes patients fasting during Ramadan - Shete, Abhijit (Baishideng Publishing Group Co., Limited, 2013)
AIM: To compare the use of vildagliptin and sulfonylurea with or without metformin in Indian Muslim patients with type 2 diabetes mellitus, fasting during Ramadan. METHODS: This was a 4-wk, multicenter, non-interventional, open-label, observational study. Incidence of hypoglycemic events (HEs), adverse events, and changes in glycosylated hemoglobin A1c (HbA(1c)), fasting plasma glucose, postprandial plasma glucose and body weight were measured pre- and post-Ramadan. RESULTS: Totally, 97 patients were recruited and all completed the study (vildagliptin group, n = 55; sulfonylurea group, n = 42). HEs were reported in low frequencies in both the vildagliptin and the sulfonylurea groups [0 vs 2 (4.8%) patients, respectively]. Interestingly, HbA1c reduced by -0.43% (-4.71 mmol/mol) in the vildagliptin group [8.75% (72.10 mmol/mol) to 8.32% (67.38 mmol/mol), P = 0.009] while in the sulfonylurea group there was a small increase by 0.01% [0.08 mmol/mol; 8.64% (70.92 mmol/mol) to 8.65% (71.00 mmol/mol), P = 0.958]. Higher percentage of vildagliptin-treated patients achieved HbA(1c) < 7.0% (< 53 mmol/mol) compared with sulfonylurea (16.4% vs 4.8%). Mean decrease in the body weight was 1.2 kg and 0.03 kg, respectively (P < 0.001). Both treatment groups were well tolerated during Ramadan. CONCLUSION: Vildagliptin is an attractive treatment option for Indian patients with type 2 diabetes mellitus who are fasting during Ramadan.